Internal jugular venous aneurysm—A report of two cases with literature review - Tamas Kovacs, MD; Salah El Haddi, MD; W. Anthony Lee, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2020)
Internal jugular venous aneurysm (IJVA) is a rare entity that usually remains asymptomatic with only rare complications. We report two cases of IJVA. Both patients presented with a palpable soft tissue mass in the neck and were found to have IJVA on imaging with associated lymphadenopathy. In both cases, the aneurysms and involved lymph nodes were resected, with the jugular vein being primarily reconstructed. There are only a few case reports involving IJVA, and treatment guidelines are not well established. Whereas nonoperative management is frequently chosen, the most common indication for surgery is cosmetic; both management options have favorable outcomes.